Dental caries; its sequelae and treatment among patients in a tertiary hospital in north–western Nigeria: A retrospective study - Bala M; Edeji CB; Braimah RO; Jaafaru R; Abubakar MK; Taiwo AO; Bawa AT (Ibom Medical Journal, 2023)
Background: Dental caries has been the most prevalent dental disease that affect human dentition. Lack of early visitation to the dentist and, awareness could lead to tooth mortality. This study aims to describe the pattern of dental caries, sequelae and, treatment among patients attending the dental clinic of Yariman Bakura Specialist Hospital Gusau (YBSH).